Inquiry Training Learning Model Assisted by Google Classroom to Improve Creative Thinking Skills of Senior High School Students - Hariadi, M. Helmi; Jumadi, Jumadi; Wilujeng, Insih; Kuswanto, Heru; Wulandari, Wulandari; Sundari, Sri (JPI (Jurnal Pendidikan Indonesia), 2019)
This study aimed at determining the effect of the inquiry training learning model assisted by Google Classroom in improving students' creative thinking skills. This research was quasi-experimental. Total samples were 32 students of SMAN 1 Banguntapan. The instrument test was essay test to measure the creative thinking skills. The first step of study was the given the pretest, then face-to-face learning and online learning at the time agreed upon with students. The final stage was carried out posttest to see the achievement of score after treatment. The results showed that the gain scores of creative thinking skill in students are categorized into three, namely: 62% of students with low category gain scores, 31% of students with moderate category gain scores, and 7% of students with high category gain scores. The average score of gain of creative thinking ability was 0.3 which was in the medium category. Based on these results, further research is needed with an emphasis on optimizing the use of Google Classroom and confirming knowledge construction in face-to-face learning.